2001
DOI: 10.1128/jb.183.17.5145-5154.2001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Streptococcus salivarius ptsH Mutants That Can Be Isolated in the Presence of 2-Deoxyglucose and Galactose and Characterization of Two Mutants Synthesizing Reduced Levels of HPr, a Phosphocarrier of the Phosphoenolpyruvate:Sugar Phosphotransferase System

Abstract: In streptococci, HPr, a phosphocarrier of the phosphoenolpyruvate:sugar phosphotransferase transport system (PTS), undergoes multiple posttranslational chemical modifications resulting in the formation of HPr(HisϳP), HPr(Ser-P), and HPr(Ser-P)(HisϳP), whose cellular concentrations vary with growth conditions. Distinct physiological functions are associated with specific forms of HPr. We do not know, however, the cellular thresholds below which these forms become unable to fulfill their functions and to what ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Wild-type S. salivarius cells immediately stop the uptake of the non-PTS sugar lactose or galactose when glucose or fructose is added to the growth medium and resume the metabolism of the non-PTS sugars only when glucose or fructose is exhausted (660). In contrast, the uptake of lactose or galactose by the ptsH mutants containing twofold-lower amounts of P-Ser-HPr was not affected by the presence of the PTS sugar glucose or fructose (870). To exert inducer exclusion, gram-positive bacteria therefore seem to require high levels of P-Ser-HPr.…”
Section: Is P-ser-hpr Involved In Inducer Exclusion?mentioning
confidence: 67%
See 1 more Smart Citation
“…Wild-type S. salivarius cells immediately stop the uptake of the non-PTS sugar lactose or galactose when glucose or fructose is added to the growth medium and resume the metabolism of the non-PTS sugars only when glucose or fructose is exhausted (660). In contrast, the uptake of lactose or galactose by the ptsH mutants containing twofold-lower amounts of P-Ser-HPr was not affected by the presence of the PTS sugar glucose or fructose (870). To exert inducer exclusion, gram-positive bacteria therefore seem to require high levels of P-Ser-HPr.…”
Section: Is P-ser-hpr Involved In Inducer Exclusion?mentioning
confidence: 67%
“…An approximately twofold decrease in the P-Ser-HPr level was reported to lead to an almost complete loss of inducer exclusion in S. salivarius cells (870). The lower amount of P-Ser-HPr was due to specific point mutations in the ptsH gene or the ptsH leader sequence, which did not affect the uptake rate of PTS substrates, although the metabolism of PTS sugars was slowed.…”
Section: Is P-ser-hpr Involved In Inducer Exclusion?mentioning
confidence: 95%
“…Although there is no direct evidence that S. salivarius LacS is regulated by HPr(Ser-P), it was demonstrated that the I47T substitution in S. salivarius HPr inhibits the preferential metabolism of glucose and fructose over lactose (10), indicating that somehow HPr is involved in the regulation of LacS. Moreover, a CcpA binding site (cre sequence) has been identified in the promoter region of the S. salivarius gal operon (40), and reduction in the levels of intracellular HPr by a factor of 3 interferes with expression of the gal operon (33). Lastly, we cannot rule out that S. salivarius possesses a second, as-yet-unidentified galactose transporter that would allow growth of mutant G71 on galactose.…”
Section: Discussionmentioning
confidence: 99%
“…HPr(HisϳP) accomplishes its regulatory functions by reversibly phosphorylating its targets, and HPr(Ser-P) accomplishes its regulatory functions by protein-protein interactions (7,13,31,42). In addition to the aforementioned phosphorylated forms of HPr, rapidly growing streptococcal cells contain substantial amounts of the doubly phosphorylated form HPr(Ser-P)(HisϳP), whose functions remain unclear (33,36,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation